Impact of the COVID-19 Pandemic and Lockdown on Anxiety, Depression and Nursing Burden of Caregivers in Alzheimer's Disease, Dementia With Lewy Bodies and Mild Cognitive Impairment in China: A 1-Year Follow-Up Study - Bao, Xinran; Xu, Junying; Meng, Qingbo; Gan, Jinghuan; Wang, Xiao-Dan; Wu, Hao; Liu, Shuai; Ji, Yong (Frontiers in Psychiatry, 2022)
Background Many countries have adopted lockdown strategies to prevent the spread of COVID-19. The goal of this study was to investigate the effects of the pandemic on anxiety, depression and care burden in caregivers of nursing patients with Alzheimer's disease (AD), Dementia with Lewy Bodies (DLB) and Mild Cognitive Impairment (MCI), over a one-year period. Methods We collected data on consecutive patients and their caregivers recruited at T0 (from 30 September to 31 December 2019) before the pandemic of COVID-19 at the memory clinic of Tianjin Huanhu Hospital. The patients and caregivers were followed up on face-to-face at T1 (from 30 September to 31 December 2020) during the pandemic to assess changes in physical activity, social contact, sleep quality, caregiver burden, anxiety and depression. Results A total of 105 AD, 22 DLB and 50 MCI patients and caregivers were enrolled. A total of 36.6 % of the AD, 81.6% of the DLB, 38% of the MCI caregivers had worsening ZBI, whereas 31.7 % of the AD, 54.4% of the DLB, 26 % of the MCI caregivers had worsening GAD-7, and 29.6 % of the AD, 54.4% of the DLB, and 32 % of the MCI caregivers had worsening PHQ-9. DLB caregivers exhibited a rapid deterioration of ZBI (by 4.27 ± 5.43, P < 0.001), GAD-7 (by 2.23 ± 3.26, P = 0.003) and PHQ-9 (by 1.32 ± 2.25, P = 0.003) compared to AD and MCI caregivers. Conclusion Social isolation, physical inactivity and sleep disturbance after lockdown for at least 12 months were significantly related to increased caregiver burden and worsened psychological states of caregivers of AD, DLB and MCI sufferers, especially among DLB caregivers.